Strength improvement of mortar incorporated dredged sediment for sustainable construction - Abdul Rahman, Muhammad Naufal; Masjuki, Siti Aliyyah; Saad, Siti Asmahani; Md. Husain, Nadiah; Beddu, Salmia (Kulliyyah of Engineering, International Islamic University Malaysia, 2024)
This paper discussed on the performance of mortar incorporated dredged sediment as a partial replacement to sand for sustainable construction materials. For that purpose, several tests were conducted to determine the properties of fresh and hardened mortar incorporated dredged sediment. Sieve analysis, bulk density, plunger penetration test, dry bulk density, compressive strength test and water absorption test were performed in this research. The study was conducted by comparing fresh and hardened properties of conventional mortar to mortars incorporated with dredged sediment by 10%, 20% and 30% replacement. The results indicated a promising outcome since some of the properties of mortar incorporated dredged sediment improved. The study found out that the optimum percentage of dredged sediment as replacement of sand to be 10%. It is proven that the incorporation of dredged sediment as partial replacement of sand in the production of mortar can improve the strength of mortar.